The relationship between non-financial reporting, environmental strategies and financial performance: Empirical evidence from Milano stock exchange - Simone Pizzi (Administrative Sciences, 2018)
The CSR theme has taken on an increasingly central role within financial markets. In fact, the last decade has been characterized by a rapid development of "socially responsible" investment, conventionally known as SRI. In this sense, an increasing number of listed firms have reported their non-financial information to the purpose to favor the interaction with their stakeholders. The relevance of these information tools stems from the need to protect investors against companies operating through greenwashing mechanisms. The aim of this research is to assess the effect of CSR on financial economic performance. As already happened within similar studies concerning economic entities different from Italy, the study assesses how the ability to generate income, and, thus, to distribute value towards the shareholder, are influenced by the orientation of companies in the field of sustainability accounting and the aptitude to check the environmental risk associated with the exercise of business activity.
Keywords: 350; corporate social responsibility; greenwashing